Differential expression analysis of lncRNA and mRNA in ovarian tissues of Pishan Red Sheep and Hu Sheep with distinct genotypes during estrus - Muhetaer, Aisima; Gong, Gao; Ye, Yaoyang; Kuxitaer, Ayipare; Zhu, Mengting; Li, Qifa; Du, Xing; Sulaiman, Yiming (Frontiers in Veterinary Science, 2025)
Pishan Red Sheep and Hu Sheep are sheep breeds with exceptional reproductive characteristics. To investigate the similarities and differences in the expression of reproduction-related genes between these two breeds, this study utilized transcriptome sequencing to identify differentially expressed lncRNAs and mRNAs in ovarian tissues during estrus in Hu Sheep and Pishan Red Sheep carrying FecBB+ and FecB++ genotypes. Furthermore, we explored their potential impacts on fertility. Transcriptome sequencing of ovarian tissues generated 204.58 Gb of clean data. Bioinformatics analysis identified 34,651 lncRNAs, with differential expression analysis revealing 1,481 differentially expressed mRNAs and 698 differentially expressed lncRNAs. Differentially expressed RNAs associated with reproductive performance trends were screened through expression trend analysis. Functional enrichment analysis of target genes for these mRNAs and lncRNAs revealed significant enrichment in KEGG pathways such as “Cytokine-cytokine receptor interaction,” “Hippo signaling pathway” and “MAPK signaling pathway” Key candidate mRNAs were identified, including GDF9, GRIA4, HOXC9, HOXD3, MAPK8IP3, AMH, ANGPT2, FGF14, MAPK8IP1, MMP9, and BRINP3. Additionally, critical regulatory relationships between lncRNAs and mRNAs were uncovered. For example, MSTRG.61044.1 exhibited high expression in FecB++ genotype Pishan Red Sheep and may act as a hub regulator in follicular selection and hormonal responses by cis-regulating MAPK8IP1 and trans-regulating AMH, CCL25, MSTRG.23016.1 may regulate genes such as MMP9 and ANGPT2, potentially participating in the modulation of the ovarian tissue remodeling microenvironment. In contrast, MSTRG.15154.3 cis-regulates ERBB4 to modulate the granulosa cell proliferation and differentiation process. The specifically highly expressed MSTRG.2677.1 in Hu Sheep may be involved in maintaining ovarian stromal cell homeostasis through trans-regulation of HGF and BRINP3, MSTRG.27015.1 and MSTRG.60286.1 target MAPK8IP3 and PPP3CB respectively, suggesting their potential roles in cell cycle regulation and oocyte maturation. These findings provide important molecular mechanisms and potential regulatory targets for improving reproductive performance in sheep.